2015
DOI: 10.1186/s12959-015-0064-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors in patients with deep venous thrombosis, a retrospective case control study on Iranian population

Abstract: BackgroundVenous thromboembolism (VTE) could be manifested as deep venous thrombosis (DVT) or pulmonary embolism (PE). DVT is usually the more common manifestation and is usually formation of a thrombus in the deep veins of lower extremities. DVT could occur without known underlying cause (idiopathic thrombosis) which could be a consequence of an inherited underlying risk factor or could be a consequence of provoking events, such as trauma, surgery or acute illness (provoked thrombosis). Our aim in this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
10
2
2
Order By: Relevance
“…Likewise, another meta-analysis involving approximately 120,000 cases and 180,000 controls found a significant 57% increased risk of VTE in C677T homozygotes compared with heterozygotes and wild-types, in a Chinese population, whereas in Caucasians no significant association was found [11]. The MTHFR A1298C polymorphism is less well characterized but also reported to lead to increased VTE risk in the Iranian population [12]. However, conflicting results exist, and hence the role of MTHFR polymorphism in VTE is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, another meta-analysis involving approximately 120,000 cases and 180,000 controls found a significant 57% increased risk of VTE in C677T homozygotes compared with heterozygotes and wild-types, in a Chinese population, whereas in Caucasians no significant association was found [11]. The MTHFR A1298C polymorphism is less well characterized but also reported to lead to increased VTE risk in the Iranian population [12]. However, conflicting results exist, and hence the role of MTHFR polymorphism in VTE is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombosis formation is influenced by PAI-1 gene polymorphisms. [ 24 ] Accumulating evidences have suggested that the PAI-1 gene 4G/5G polymorphism might be an etiological factor for ON occurrence in renal transplant patients, [ 25 ] post-SARS patients [ 26 ] and glucocorticoid-induced ON patients. [ 27 ] There also other polymorphisms exist in the PAI-1 gene, such as rs6092 (exon 1) and rs7242 (3′UTR).…”
Section: Discussionmentioning
confidence: 99%
“…было обнаружено, что инфаркт миокарда, возможно, является независимым от других факторов риска предиктором ВТЭ [147]. Кроме того, недавно с помощью полногеномных исследований были обнаружены неизвестные ранее тромбогенные мутации, связанные не только с ВТЭ, но и с артериальными тромбозами [148,149]. В свою очередь, исследования Sumner и др.…”
Section: прогнозирование риска втэ на фоне гормональной контрацепции unclassified